PENGARUH SEGMENTASI, TARGETING, DAN POSITIONING TERHADAP KEPUASAN KONSUMEN PADA PRODUK BERAS UD. GOTONG ROYONG DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - Anam, Muhammad Mishbahul; Tulhusnah, Lusiana; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The tightness of market competition makes it a challenge in this modern era. Therefore, in a market there are several firms that produce similar products. Rice products are a big concern in the competition. Strategy and market analysis must be mobilised to achieve a target. The purpose of this study was to examine and examine the influence of the Effect of Segmentation, Targeting, and Positioning on Consumer Satisfaction on UD Rice Products. Gotong Royong with purchasing decisions as an intervening variable. The research population uses all UD consumers. Gotong Royong according to the data that the researcher has requested from the owner of the research site. The sampling method uses probability sampling. Data analysis and research hypothesis testing using the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3. 0, shows that Segmentation has a negative but insignificant effect on purchasing decisions, (H1 rejected); Targeting has a positive but insignificant effect on purchasing decisions, (H2 rejected); Positioning has a significant positive effect on purchasing decisions, (H3 accepted); Segmentation has a positive but insignificant effect on customer satisfaction, (H4 rejected); Targeting has a significant positive effect on customer satisfaction, (H5 accepted); Positioning has a significant positive effect on customer satisfaction, (H6 accepted); Purchasing decisions have a significant positive effect on customer satisfaction (H7 accepted); Segmentation has a negative but insignificant effect on customer satisfaction through purchasing decisions, (H8 rejected); Targeting has a significant positive effect on customer satisfaction through purchasing decisions, (H9 accepted); Positioning has a significant positive effect on customer satisfaction through purchasing decisions, (H10 accepted).